Antioxidant Enzyme Activities as a Tool to Discriminate Ecotypes of Crithmum maritimum L. Differing in Their Capacity to Withstand Salinity - Karim, Ben Hamed; Christian, Magné; Chedly, Abdelly (IntechOpen, 2012)
None